Pharmaco-genomic investigations of organo-iridium anticancer complexes reveal novel mechanism of action. Issue 1 (13th November 2017) - Hearn, Jessica M.; Hughes, George M.; Romero-Canelón, Isolda; Munro, Alison F.; Rubio-Ruiz, Belén; Liu, Zhe; Carragher, Neil O.; Sadler, Peter J.
Abstract : Transcriptomic, phenotypic and high throughput data reveal unique anticancer mechanisms shared by organometallic iridium and osmium complexes. Abstract : Resistance to platinum drugs (used in >50% of cancer chemotherapies) is a clinical problem. Other precious metal complexes with distinct mechanisms of action might overcome this. Half-sandwich organometallic complexes containing arene or cyclopentadienyl (Cp) ligands show promise. We screened two iridium(iii ) complexes [Ir(Cp Xbiph )(ppy)Cl] (ZL49, 1, ppy = phenylpyridine) and [Ir(Cp Xph )(azpyNMe2 )Cl]PF6 (ZL109, 2, azpyNMe2 = N, N -dimethylphenylazopyridine) in 916 cancer cell lines from 28 tissue types. On average, complex2 was 78× more potent than1, 36× more active than cisplatin (CDDP), and strongly active (nanomolar) in patient-derived ovarian cancer cell lines. RNA sequencing of A2780 ovarian cells revealed upregulation of antioxidant responses (NRF2, AP-1) consistent with observed induction of reactive oxygen species (ROS). Protein microarrays, high content imaging and cell cycle analysis showed S/G2 arrest, and late-stage DNA damage response without p53 requirement. The triple-negative breast cancer cell line OCUB-M was highly sensitive to2 as were cell lines with KIT mutations. Complex2 exhibits a markedly different pattern of antiproliferative activity compared to the 253 drugs in the Sanger Cancer Genome database, but is most similar to osmium(ii ) arene complexes which share the same azopyridine ligand. Redox modulation and DNA damage can provide a multi-targeting strategy, allowing compounds such as2 to overcome cellular resistance to platinum anticancer drugs.